Analisis Pengaruh Desain Eksterior dan Cita Rasa Terhadap Keputusan Pembelian pada Café Kokoro - Gustina, Ihdina (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to find out how much influence the exterior design and taste have on purchasing decisions at Cafe Kokoro. The research methodology used is a quantitative descriptive method, the unit of analysis in this study is Cafe Kokoro. The technique for determining the number of samples used in this study uses the Slovin formula and amounts to 150 respondents. The research method used is the technique of collecting data through library research and field research which is carried out systematically based on the research objectives. The analysis method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. This analysis includes validity and reliability, classical assumption tests, multiple regression analysis, hypothesis testing through t and F tests, and determination coefficient tests (R2). The results of the t test show that the Exterior Design variable 16.076> t table 1.655 and the Taste variable has no significant effect on Purchasing Decisions at Cafe Kokoro where t count 2.644> t table 1.655. The results of the F test show that Fcount 156.293 > Ftable 2.34, which means that the independent variables, namely Exterior Design and Taste, simultaneously influence the dependent variable, namely the Purchase Decision at Cafe Kokoro. The results of the determination coefficient test (R2) show that 68% of the Purchase Decision variable at Cafe Kokoro is influenced by the Exterior Design and Taste variables, while the remaining 32% is explained by the influence of other factors or variables outside the model such as Excellent Service, Service Quality and Price which are not discussed in this study